Arfict: Indoor navigation mobile application using augmented reality (AR) for FICT - Lee, Chorng Huah (2025)
As commercial and educational institutions grow more complex, indoor navigation has become essential. Traditional GPS navigation, effective outdoors, struggles indoors due to signal interference from walls and ceilings. This is even more significant in large, multi-floor buildings such as university campuses, where GPS signals are blocked. Additionally, 2D maps are not capable of providing real-time, adaptive directions, leading to inefficiency and user frustration. Hence, the ARFICT project aims to develop an Augmented Reality (AR)-based indoor navigation system for the FICT building at UTAR, providing a real-time, interactive navigation experience that enhances wayfinding in complex indoor environments. The project's contribution goes beyond UTAR, forming a basis for AR-based navigation in various large indoor environments, such as shopping malls, airports, and hospitals. The use of external hardware, like Bluetooth beacons, is eliminated, thus offering an affordable solution for navigation in multi-floor buildings. The system employs a marker-based localisation method using QR codes decoded with the ZXing library to establish the user’s initial position. Navigation paths are optimised using the A* algorithm, while ARCore integrates sensor data from the device’s gyroscope and accelerometer to enhance tracking accuracy. Users are guided with AR-based path visualisation, distance indicators, and voice instructions, ensuring intuitive and efficient navigation across multiple floors. In summary, this project successfully developed an AR indoor navigation application to provide advanced indoor navigation, improve efficiency, and provide a reliable wayfinding for students, staff, and visitors in the multi-floor FICT building, enhancing the user experience in complex indoor environments.